Microsatellite primers for the gynodioecious grassland perennial Saxifraga granulata (Saxifragaceae)1. (29th August 2014) - van der Meer, Sascha; Van Houdt, Jeroen K. J.; Maes, Gregory E.; Hellemans, Bart; Jacquemyn, Hans
Abstract : Premise of the study: Nine polymorphic and 12 monomorphic microsatellite loci (simple sequence repeats [SSRs]) were isolated and characterized for the gynodioecious grassland perennial Saxifraga granulata . Methods and Results: Based on genomic screening of leaf material of four individuals from four populations, a total of 21 microsatellite primer pairs were designed for S. granulata . Nine loci were polymorphic and were optimized into two PCR multiplex reactions and tested on 100 individuals from five riparian populations from central Belgium. The number of alleles of the polymorphic loci ranged from three to 18, and gametic heterozygosity ranged from 0.26 to 0.94. Conclusions: The markers that are presented here are the first microsatellite markers reported for S. granulata and will be used to assess how river systems shape the spatial genetic structure and diversity of riparian populations of this species.